Handbook of research on technologies and systems for e-collaboration during global crises - Zhao, Jingyuan; Kumar, V Vinoth (Advances in social networking and online communities (ASNOC) book series, 2022)
"This book focuses on emerging technologies and systems, strategies and solutions for e-collaboration especially highlighting the importance of technologies and systems for e-collaboration in dealing with emerging crisis such as unpredicted pandemic diseases like COVID -19.